Use of tic in higher education of geography at distance - Losekann, Marilse Beatriz (Geosaberes; Vol 9 No 18 (2018): May - Aug.DO - 10.26895/geosaberes.v9i18.638, 2018)
This work presents the study about the use of Information and Communication Technologies (TIC) by the professors of the Graduate Course in Geography of the Federal University of Santa Maria (UFSM), in the distance modality. The qualitative approach was based on research and the instruments used were documentary research and the questionnaire. The results show that 57.1% of the teachers have specific training for the use of TIC and among the most used tools are the text editor and the slide show, which shows the underutilization of TIC. In relation to social networks, half of the teachers make use of these, with Facebook and Whatsapp being the most employed. The TIC is part of the pedagogical daily life in the UAB/UFSM Geography course, however, its potential and the existing diversity of educational technologies are not explored.
Keywords: Tecnologia de Informação e Comunicação, Geografia, Formação de professores, Educação à distância.